2016
DOI: 10.18805/lr.v0iof.10759
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and characterization of pigeonpea stem rot disease caused by Sclerotinia sclerotiorum (lib.) de bary in North Eastern Plain Zone of India

Abstract: The incidence of Sclerotinia rot disease was recorded on various pigeonpea cultivars from flowering initiation to pod formation stage during the years 2012-13 and 2013-14. Critical symptoms of the disease were observed as formation of cottony white mycelium along with number of sclerotia on infected tissues. The pathogen was characterized on the basis of morphological and pathological traits. The cool wet winter with average minimum and maximum temperatures (9.2 and 21.0 ºC) and more than 93% relative humidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The amplified products of ITS and species-specific primers were partially sequenced and identified as S. sclerotiorum by comparing sequences available in NCBI database. Similarly, Gupta et al, (2016) and Kumar et al, (2015) confirmed the fungus S. sclerotiorum by molecular characterization using ITS and species specific primers using ITS and specific primers.…”
Section: Phylogenetic Analysis Of S Sclerotiorum Isolatesmentioning
confidence: 87%
See 1 more Smart Citation
“…The amplified products of ITS and species-specific primers were partially sequenced and identified as S. sclerotiorum by comparing sequences available in NCBI database. Similarly, Gupta et al, (2016) and Kumar et al, (2015) confirmed the fungus S. sclerotiorum by molecular characterization using ITS and species specific primers using ITS and specific primers.…”
Section: Phylogenetic Analysis Of S Sclerotiorum Isolatesmentioning
confidence: 87%
“…Presently, disease control strategies include chemical control and cultivar resistance, but both of them lead to pathogen resistance development. The pathogen is highly challenging to manage because of its survivability in the resting structure called sclerotia which has a great significance in disease epidemiology (Gupta et al, 2016). The germination of these sclerotia, which typically occurs at the soil surface, can result in the production of massive amounts of highly infectious spores, which disseminate the pathogen via air currents and cause infections on the leaves.…”
Section: Introductionmentioning
confidence: 99%